What's wrong in the control of antimicrobial resistance in critically ill patients from low- and middle-income countries? - Dondorp, A; Limmathurotsakul, D; Ashley, E (Springer International Publishing AG, 2017)
Critical care environments are magnets for drug-resistant organisms. Patients are extremely vulnerable to nosocomial infections due to the severity of their clinical condition, the siting of multiple invasive medical devices and their proximity to other infected patients. Use of broad spectrum antibiotics is high in intensive care units (ICUs) compared to other hospital departments, making selection of drug-resistant bacteria more likely. In low- and middle-income countries (LMICs), nosocomial infections are thought to be more common than in high-income countries (HICs), although objective incidence rates are unknown, since routine bacteriological surveillance does not usually occur. In tropical settings, severe malaria is a common cause of sepsis, and antimalarial drug resistance is an increasing problem. Here, we give our perspective on the important threat of antimicrobial drug resistance (AMR) in critical care patients in LMICs, contributing factors and initiatives to address this. For further reading, we refer to the supplement listing additional references.